Uniform auxin triggers the Rho GTPase-dependent formation of interdigitation patterns in pavement cells - Xu, Tongda (Landes Bioscience, 2011)
The investigation of Rho-family GTPases has uncovered mechanisms for spatiotemporal control of cellular processes such as cell polarization, movement, morphogenesis and cell division. Now Rho GTPase plays another leading role in the discovery of a new signaling mechanism for auxin, a multifunctional hormone that regulates pattern formation in plants. Arabidopsis leaf epidermal pavement cells (PCs) develop the puzzle-piece cell shape with interlocking lobes and indentations via interdigitated cellular growth.1 Through the ABP1 (Auxin Binding Protein 1) cell surface receptor, auxin coordinately activates 2 mutually exclusive Rho GTPase signaling pathways that are activated in the complementary lobing and indenting sides of adjacent cells: the ROP2 pathway for lobe formation and the ROP6 pathway for promoting indentation. This new signaling mechanism also involves ROP2-dependent polar accumulation of PIN1 in the plasma membrane, a member of the PIN auxin efflux carrier family that is critical for the formation of various developmental patterns including the PC interdigitation pattern. This Rho-dependent auxin signaling mechanism explains how interdigitated cellular growth is coordinated. In this extra view, we propose that the same mechanism can also explain how a uniform auxin signal initiates the formation of the interdigitated pattern.